2007
DOI: 10.1007/s00213-007-0831-y
|View full text |Cite
|
Sign up to set email alerts
|

Diphenyl diselenide decreases the prevalence of vacuous chewing movements induced by fluphenazine in rats

Abstract: Our data suggest that the reduction in dopamine transport can be a possible mechanism related to the maintenance of VCMs in rats. Moreover, diphenyl diselenide seems to be a promising pharmacological agent in the reduction in the prevalence of VCMs in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Moreover, several studies using inorganic and organic forms of Se have demonstrated their protective effects against oxidative stress in disease models of diabetes (Kiersztan et al, 2007), cancer (Steinbrenner and Sies, 2009) and neurological disorders (Atif et al, 2008). In fact, different classes of Se compounds such as Ebselen, a lipid soluble seleno‐organic compound, (Porciúncula et al, 2001), as well as other organic Se (Nogueira et al, 2004; Fachinetto et al, 2007) and inorganic Se such as sodium selenite (Atif et al, 2008) exhibit a neuroprotective role via their antioxidant properties, making Se an essential trace element.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several studies using inorganic and organic forms of Se have demonstrated their protective effects against oxidative stress in disease models of diabetes (Kiersztan et al, 2007), cancer (Steinbrenner and Sies, 2009) and neurological disorders (Atif et al, 2008). In fact, different classes of Se compounds such as Ebselen, a lipid soluble seleno‐organic compound, (Porciúncula et al, 2001), as well as other organic Se (Nogueira et al, 2004; Fachinetto et al, 2007) and inorganic Se such as sodium selenite (Atif et al, 2008) exhibit a neuroprotective role via their antioxidant properties, making Se an essential trace element.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment was carried out over the course of 6 months and was based on previous studies [4,29,[41][42][43].…”
Section: Methodsmentioning
confidence: 99%
“…The simplest of diaryl diselenides, diphenyl diselenide, has been shown to be even more active as a glutathione peroxidase mimic [27] and less toxic to rodents than ebselen [28]. Recently, data from our laboratory have indicated that diphenyl diselenide decreased the prevalence of vacuous chewing movements induced by long‐term treatment with fluphenazine in rats [29]. Furthermore, diphenyl diselenide has a protective role in a variety of experimental models associated with the overproduction of free radicals in the brain, liver and kidney [26,30–32].…”
mentioning
confidence: 99%